Analysis of the Phenomenon of Corruption in the World of Educators: A Review of Solution-Based Cases from the Perspective of Positive Law - Mahmud, Gita (Judge : Jurnal Hukum, 2024)
This study aims to analyze the phenomenon of corruption in the educational sector in Indonesia, focusing on the relationship between the legitimacy of educational policies and the corruption practices that occur. Corruption in the education sector can undermine the integrity and transparency of policies, hinder the effectiveness of budget allocation, and degrade the quality of educational services. This research identifies several common forms of corruption, including budget misuse, non-transparent procurement of goods and services, and collusion in educational decision-making. Using a positive law perspective, the study proposes solution-oriented measures to address corruption in education, such as enhancing transparency, strengthening internal oversight, providing anti-corruption education and training, and encouraging active community participation. Moreover, strict law enforcement and collaboration between educational institutions and law enforcement agencies are deemed crucial to establishing an education system free from corruption. The study concludes that through these concrete measures, it is expected to improve the quality of education in Indonesia, strengthen the legitimacy of educational policies, and increase public trust in the existing education system.